REVITALIZING THE ROLE OF MOTHERS AS CHILDREN'S FIRST SCHOOL - Chusna Apriyanti (JURNAL EDUSCIENCE (JES), 2021)
This study aims to determine the mothers' role in family life in Pacitan Regency, East Java and the ways to revitalize the mother’s role. This is descriptive quantitative research. Data were collected by using a questionnaire of 74 women of childbearing age. This research was conducted in December 2020. In addition, the data were taken from interviews with respondents using a random sample technique. After being collected, the data is described in charts and conclusions drawn. The results showed that the mother has three main roles: fulfilling the children's needs, being a role model, and stimulating children's development. Criteria for fulfilling the children's needs is measured by indicators: mothers cook breakfast for children, pick up children from school, accompany children to play ; 2) Mother as a role model for children; and 3) Mothers provide a stimulus to the children's development seen from the time accompanying their children to study, buy children story books and stationery, time to play gadgets.Keywords: Career Woman, Double Role Mother, Mother’s Role